Hubungan Minat dan Kemandirian dengan Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 8 Palangka Raya - Septi Ganefi; Sugiharto Sugiharto; Rizki Nurhana Friantini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2026)
This research is motivated by the low learning outcomes of students, the lack of interest in learning mathematics, and the lack of independence in learning mathematics. The objectives of this research are to determine: 1) the positive relationship between learning interest and mathematics learning outcomes, 2) the positive relationship between learning independence and mathematics learning outcomes, 3) the positive relationship between interest and independence and mathematics learning outcomes. This research uses a quantitative approach with a correlational research type. The population in this study were 363 students of class VIII of SMP Negeri 8 Palangka Raya and the research sample consisted of 208 students. Before use, the instrument was tested with 58 students. The trial results obtained for the learning interest questionnaire were 30 valid with a reliability coefficient of r11=0,88. For the learning independence questionnaire, 28 were valid with a reliability coefficient of r11=0,85 . For the learning outcome test, 22 were valid with a reliability coefficient of r11=0,72. The analysis requirement test, namely the data normality test with Kolmogorov-Smirnov, obtained three data with normal distribution. From the results of the hypothesis test, it shows that: (1) there is a significant positive relationship between learning interest and students' mathematics learning outcomes, the correlation coefficient is rX1Y =0,1493, the significance test is thitung=2,167; (2) there is a significant positive relationship between learning independence and students' mathematics learning outcomes, the correlation coefficient is rX2Y =0,1441, the significance test is thitung=2,061; (3) there is a significant positive relationship between learning interest and independence with students' mathematics learning outcomes, the correlation coefficient is RY(X1X2)=0,1759, the significance test is Fhitung=3,271.